Microbiological and Nutritional Evaluation of Fermented Setipinna Species - Sarojnalini, Ch; T., Suchitra (Fishery Technology, 2025)
Biochemical composition, digestibility and microbiological quality of fermented Setipinna sp. were evaluated. The average percentage of moisture, total protein, lipid, ash content and pH values were 36.44, 36.25, 6.66, 10.22 and 7.68 respectively. Thiobarbituric acid number was within the permitted level, but total volatile basic nitrogen values were above the acceptable limits. In vitro digestibility of fermented Setipinna was 54.11 percent in pepsin phase and 82.78 percent in pepsin + trypsin phase in comparison with the value for casein of 98.03 percent in pepsin + trypsin phase. Apparent digestibility value of fermented fish was 83.72 percent as against the value of 87.20 percent for reference casein. Colony forming unit of bacteria and fungus reached up to 5.74 log cfu/g and 3.28 log cfu/g respectively. The predominant bacteria include Bacillus and Micrococcus species. Pathogenic bacteria viz. Staphylococus aureus, faecal Streptococci were detected above the permitted level but coliform, E coli and Salmonella were not detected. Aspergillus, Penicillium, Rhizopus Cladosporium and Fusarium were the fungi isolated from fermented fish.